Yi Gong San inhibits tumor immune escape by sensitizing colorectal cancer stem cells via the NF-κB pathway - Peng Shen; Shunli Wu; Yi Chen; Guangjing Feng; Xue Guo; Yingguo Chen; Zhigang Wang; Youfeng Shen; Hongbo Wang; Ke Li (Hereditas)
Abstract Objective Colorectal cancer (CRC), as a highly prevalent malignant tumor globally, faces the dual challenges of drug resistance of cancer stem cells and immune escape in its treatment. Although the traditional Chinese medicine Yigong San (YGS) shows potential in improving the clinical adverse reactions of CRC, its core active components and mechanism of action remain unclear. Based on network pharmacology screening, this study for the first time discovered that Gomisin B might regulate the progression of CRC through the Toll-like receptor 4/Nuclear Factor-kappa B (TLR4/NF-κB) signaling pathway, and aimed to systematically reveal the molecular mechanisms by which YGS and Gomisin B inhibited the malignant phenotypes and immune escape of CRC cells. Methods The The Cancer Genome Atlas (TCGA) database was integrated with network pharmacology analysis to screen for the key target of CRC, Gomisin B, and its associated TLR4/NF-κB pathway. Through in vitro CRC stem cell models and mouse xenograft tumor models, techniques such as CCK-8, Transwell, flow cytometry, qPCR/WB were used to evaluate the effects of YGS and Gomisin B on proliferation, migration, invasion, apoptosis, and epithelial-mesenchymal transition (EMT), and to detect the expression of TLR4 and downstream inflammatory factors. Results Both YGS and Gomisin B inhibited the proliferation, migration and invasion of CRC stem cells and tumor tissues. Meanwhile, they promoted apoptosis but reduced the expression of the inflammatory factor TLR4 and proteins associated with the NF-κB pathway, thereby exerting suppressive effects on tumorigenesis and disease progression. YGS might also impede EMT progression through modulation of the NF-κB pathway. Conclusion This study for the first time elucidated the dual anti-tumor mechanisms of YGS, which sensitized CRC stem cells and inhibited immune escape by targeting the TLR4/NF-κB pathway through Gomisin B. It provides a pharmacological basis for the modern research of traditional Chinese medicine compound against CRC. Clinical trial number Not applicable.